Externalized histone H4 orchestrates chronic inflammation by inducing lytic cell death - Silvestre-Roig, Carlos; Braster, Quinte; Wichapong, Kanin; Lee, Ernest Y.; Teulon, Jean Marie; Berrebeh, Nihel; Winter, Janine; Adrover, José M.; Santos, Giancarlo Santiago; Froese, Alexander; Lemnitzer, Patricia; Ortega-Gómez, Almudena; et al. (Nature (London), 2019)
The perpetuation of inflammation is an important pathophysiological contributor to the global medical burden. Chronic inflammation is promoted by non-programmed cell death 1 , 2 ; however, how inflammation is instigated, its cellular and molecular mediators, and its therapeutic value are poorly defined. Here we use mouse models of atherosclerosis—a major underlying cause of mortality worldwide—to demonstrate that extracellular histone H4-mediated membrane lysis of smooth muscle cells (SMCs) triggers arterial tissue damage and inflammation. We show that activated lesional SMCs attract neutrophils, triggering the ejection of neutrophil extracellular traps that contain nuclear proteins. Among them, histone H4 binds to and lyses SMCs, leading to the destabilization of plaques; conversely, the neutralization of histone H4 prevents cell death of SMCs and stabilizes atherosclerotic lesions. Our data identify a form of cell death found at the core of chronic vascular disease that is instigated by leukocytes and can be targeted therapeutically. Histone H4 is released from neutrophil extracellular traps and induces membrane lysis in vascular smooth muscle cells, leading to the destabilization of atherosclerotic plaques.